Fluidic Patterning of Transparent Polymer Heaters. Issue 1 (December 2018) - Romasanta, Laura; Schäfer, Philip; Leng, Jacques
Abstract Semi-conducting polymers are promising materials for current and next generations of electronic devices, sensors and actuators, especially regarding their ability to conform to flexibles architectures. In particular, aqueous-based dispersions of semi-conducting complexes such as PEDOT:PSS can be printed using a variety of coating techniques and the conductivity of the final deposit may reach high values upon a proper treatment. The micro-structuration of these polymeric deposits remains challenging and of prime importance for further integration. We show here that a microfluidic post-treatment of PEDOT:PSS films of permits us to boostlocally only their conductivity by several orders of magnitude, with a micron scale resolution. This is a fast process (~second), straightforward to upscale, that yields conductive patterns within the pristine film. Taking advantage of the localized Joule's effect, we evidence using quantitative thermography a very efficient heating behaviour of the conductive tracks, which makes these polymeric structures promising candidates for low cost, clean-room free electrodes for lab-on-chip applications.